2011
DOI: 10.1021/jf201166b
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative Caffeoylquinic Acids and Flavonoids from Hemerocallis fulva Flowers

Abstract: Tumor necrosis factor-α (TNF-α)-induced reactive oxygen species (ROS) production in HepG2 was used to screen hepatocyte protective compounds from the flowers of Hemerocallis fulva. Three new polyphenols, n-butyl 4-trans-O-caffeoylquinate (1), kaempferol 3-O-{α-L-rhamnopyranosyl(1→6)[α-L-rhamnopyranosyl(1→2)]}-β-D-galactopyranoside (2), and chrysoeriol 7-O-[β-D-glucuronopyranosyl(1→2)(2-O-trans-feruloyl)-β-D-glucuronopyranoside (3), together with four caffeoylquinic acid derivatives (4-7), eight known flavones … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 31 publications
(50 reference statements)
3
42
1
3
Order By: Relevance
“…Other authors have reported similar effects of phenolic extracts from plants rich in monocaffeoylquinic acids such as Hemerocallis fulva (Lin, Lu, Huang, & Chen, 2011) and Corema album (León-González et al, 2012), or rich in dicaffeoylquinic acids like Gymnaster koraiensis (Jho et al, 2013) decreasing ROS generation in HepG2 cells, partially preventing the GSH depletion, antioxidant enzyme dysregulation and oxidative damage to macromolecules induced by t-BOOH, in line with the effects elicited by the YMPE.…”
Section: Discussionsupporting
confidence: 55%
“…Other authors have reported similar effects of phenolic extracts from plants rich in monocaffeoylquinic acids such as Hemerocallis fulva (Lin, Lu, Huang, & Chen, 2011) and Corema album (León-González et al, 2012), or rich in dicaffeoylquinic acids like Gymnaster koraiensis (Jho et al, 2013) decreasing ROS generation in HepG2 cells, partially preventing the GSH depletion, antioxidant enzyme dysregulation and oxidative damage to macromolecules induced by t-BOOH, in line with the effects elicited by the YMPE.…”
Section: Discussionsupporting
confidence: 55%
“…Derivatives of caffeoylquinic acid have been used to cure various diseases in traditional oriental medicine and exhibit wide ranges of biological activities, such as anti-tumor [13], hepatoprotective [14,15], anti-inflammatory [16], anti-microbial [17], and antimutagenicity activities [18], indicating that theses derivatives may exert beneficial effects against various human diseases. In addition to inhibition of human immunodeficiency virus-1 integrase and its replication [19][20][21], the antioxidant activities of caffeoylquinic acid derivatives [15,22] were also reported.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to inhibition of human immunodeficiency virus-1 integrase and its replication [19][20][21], the antioxidant activities of caffeoylquinic acid derivatives [15,22] were also reported. However, no previous study has examined the activity of methyl 3,5-di-caffeoylquinate (3,5-diCQM) (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The column temperature was set at 30 °C. A gradient mobile phase system consisting of acetonitrile:H 2 O (3:97 to 20:80 from 0 to 20 min, 20:80 to 80:20 from 20 to 22 min, 80:20 to 3:97 from 22 to 23 min, 3:97 from 23 to 27 min) with 0.1% formic acid as a modifier was used to elute the analytes after 2 μL of sample solution was applied onto the column whereas the detection wavelength was set at 340 nm [12]. The flow rate was 0.2 mL/min and the sample temperature was maintained at 4 °C.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous in vivo screening study on the active ingredients of daylily flowers, the fraction containing ~60% flavonoids exhibited significant antidepressant-like effects whereas the fraction lack of flavonoids showed no effect in mice model by forced swimming test, tail suspension test and antagonism reserpine experiments [11]. However, daylily flowers contain various types of chemical ingredients including flavonoids, phenolic acids and derivatives, di- and tri-terpenes, essential oils, steroidal saponins, alkaloids, amino acids, polysaccharides and so on [12], the potential neurological effects of other constituents in daylily flowers are largely uninvestigated. Therefore, the objectives of this study were to separate the extracts of daylily flowers into different fractions and to evaluate the neuroprotective effects of each fraction using PC12 cell damage models induced by corticosterone and glutamate with also a view to identifying the active fractions and their potential effect on the neurotransmitter release in the cell culture medium.…”
Section: Introductionmentioning
confidence: 99%